Pengaruh Pacaran terhadap Seks Pranikah di Kalangan Remaja - Wildawati (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2022)
Adolescence is a period of transition from childhood to adulthood, at that time there is rapid growth including reproductive function so that it affects changes in development, both physical, mental, and social roles. Data analysis method used in this research is statistical method and data analysis technique used is nonparametric correlation technique Contingency Coefficient (Cc). The results of the research based on the correlation coefficient of contingency (Cc) analysis, it is known that the resulting contingency coefficient shows the number 0.433.